تحديات التحول الديمق ا رطي في دولة السودان - حسين قنوعة, محمد ميلود ه (Universté ELOUEd-جامعة الوادي, 2022)
سعت الد ا رسة إلى بحث موضوع التحول الديمق ا رطي في السودان من خلال التعرض إلى أبرز التحديات التي واجهت هذا البلد والتي وقفت عائقا دون انتقال ديمق ا رطي فعلي، بالرغم من عديد المحاولات والمحطات التاريخية التي شهدها السودان الحديث والمعاصر، والتي تطلع من خلالها الشعب السوداني إلى الوصول إلى عملية ديمق ا رطية حقيقية تخرج البلاد من نفق الفساد والاستبداد السياسي والتخلف الاقتصادي والتنمويThe study sought to research the topic of democratic transition in Sudan by exposure to the most prominence challenges that faced this country and which stood as an obstacle to an actual democratic transition, despite the many attempts and historical stations witnessed by modern and contemporary Sudan, through which the Sudanese people aspired to reach a democratic process The country is coming out from the tunnel of corruption, political tyranny, and economic and developmental backwardness.
مذكرة ماستر